Case report: Pragmatic impairment in multiple sclerosis after worsening of clinical symptoms - Lago, Sara; Bevilacqua, Francesca; Stabile, Maria Rosaria; Scarpazza, Cristina; Bambini, Valentina; Arcara, Giorgio (Frontiers in Psychology, 2022)
Pragmatics, defined as the ability to integrate language and context to communicate effectively, may be impaired in Multiple Sclerosis (MS). We present the case of a patient with active secondary progressive MS who, after a first neuropsychological assessment that evidenced only a slight pragmatic impairment, suffered a sudden worsening of her clinical conditions, treated with corticosteroids. After this clinical worsening, her pragmatic abilities declined markedly, both in comprehension and production. This worsening was accompanied by a decline only in one attention task, in the context of an overall stable cognitive functioning. We conclude that pragmatics may be a domain particularly susceptible to cognitive worsening, highlighting the importance of its assessment in clinical practice.